ANALISIS KEMAMPUAN KOGNITIF PESERTA DIDIK DALAM MENYELESAIKAN SOAL MOMENTUM DAN IMPULS - Mona Nabilah; Stepanus Sahala Sitompul; Hamdani Hamdani (Universitas Tanjungpura, 2020)
This research aims to examine students’ cognitive abilities in completing physics problem about momentum and impulses at SMA Kristen Immanuel Pontianak. The research uses survey method, by giving test that consists of 11th grader (53 male; 69 female). According to the result, it was found that the total average percentage of students’ cognitive abilities in general (C1-C4) was 69% and was categorized as medium. The highest average percentage of student cognitive ability was in the domain remembering (C1) with the percentage of 90% (high) and the lowest was in the domain of analyzing with the percentage of 53% (low). Furthermore, there was difference in students’ cognitive ability based on gender in domain of remembering (C1), that was recognized from the result of Mann-Whitney statistical test (0.004<0.05), which showed that significance value was below the probability value. This research is expected to be a guide and reference in developing learning strategies in physics problem to improve students’ cognitive abilities.